Students’ Pronunciation Errors on Vowels at Spoken English Activities (Speech) Class at English Department Universitas Negeri Padang - Yon Visoni; Leni Marlina (Journal of English Language Teaching, 2020)
Pronunciation plays a significant role in effective communication. The incomprehensible pronunciation will lead to misunderstanding in communication. This present study aims to examine commonly mispronounced sounds and types of errors in the context of vowel sounds. This study investigated the pronunciation error of speech performance to get more naturalistic pronunciation as data. The source of data of this study was six speech recordings delivered by students at the speech class of spoken English activities at English Department (Universitas Negeri Padang). The recordings were analyzed to obtain pronunciation errors from the speeches. After it is done, the errors are were measured and interpreted. The result of this study revealed [æ], [i:], [ə], [əʊ], and [eɪ] were frequently made errors. These sounds were substituted as several sounds. Therefore, it is suggested that these specific errors should be taken into consideration when teaching English to L1 Indonesian EFL students.